Planning and the rule of law. (2nd July 2016) - Booth, Philip
Abstract: The impact of law in shaping the way in which spatial planning is conducted is often overlooked and attitudes to law are often purely instrumental. This paper looks at how the concept of the rule of law has evolved in England, and what effect it has had on public administration and on spatial planning processes in particular. It looks particularly at the role of equity within the common-law tradition and the way in which equitable judgment has coloured administrative decision-making. It concludes that by comparison with legal processes decision-making in spatial planning is often insufficiently rigorous.